Comparison of Biofilm Growth and Quorum Sensing Molecules in Vaginal Lactobacillus Species: A Preliminary Report - Asley Sanchez; Fnu Alimiran; Kushal Gandhi; Samuel David; Christopher B. Babayco; Chloe Fiveash; John Garza; Duc Le; Triet Le; Athenia Oldham; Douglas Henderson; Michael Galloway; et al. (Microbiology Research, 2024)
Recently, studies suggest that the protective effects of Lactobacillus within the female reproductive tract may be partly due to their ability to form biofilms. This study aims to explore the possibility that Lactobacillus can produce key mediators to further bolster the survival of biofilms in human vaginal microbiomes. Three bacterial species, namely, Lactobacillus gasseri, L. crispatus, and L. jensenii, sourced from human female subjects were used to carry out experiments examining the growth of biofilms using a microfermenter system. The bacteria were used to inoculate a glass rod spatula which was subsequently transferred to the microfermenter system. The resulting biofilm growing on the glass spatula was harvested in media and stored in a −80 °C freezer for gas chromatography–mass spectroscopy analysis. We found that quorum sensing compounds, acyl homoserine lactones (AHLs), were detected in the biofilm of L. crispatus and L. jensenii, but none were detected in L. gasseri. The biofilm produced by L. crispatus and L. jensenii was much higher in quantity than the biofilm produced by L. gasseri. Aside from oligopeptides quorum sensing, lactobacilli were found to also have AHL compounds that may help them produce more biofilms and improve the survival and growth of their bacterial communities in the female genital area.